Community‐based social care models for indigenous people with disability: A scoping review of scholarly and policy literature. (23rd September 2022) - Puszka, Stefanie; Walsh, Corinne; Markham, Francis; Barney, Jody; Yap, Mandy; Dreise, Tony
Abstract: Disability is experienced and understood by Indigenous people internationally in distinct ways from other populations, requiring different approaches in disability services. Furthermore, Indigenous populations access disability services at low rates. In response, policymakers, service providers and Indigenous organisations have developed specific models of care for Indigenous people with disability. Social care services, comprising personal care, transport and social activities, can support Indigenous people with disability to live with their families and in their communities. However, little is known about the range of social care models for Indigenous people with disability. To inform policy and practice, we conducted a scoping review of community‐based models of social care designed to meet the needs of Indigenous peoples in Australia, Aotearoa New Zealand, Canada and the United States. Our methods were informed by best practice scoping review principles and a collaborative approach that centred Indigenous voices within research appraisal and project governance processes. Literature searches (conducted March–April 2021) yielded 25 results reporting on 10 models of care. We identified two over‐arching themes (funding and governance arrangements; service delivery design) that encompass nine key characteristics of the included models. Our analysis shows promising practice in contextually relevant place‐based social activity programs, support and remuneration for family carers and workforce strategies that integrate Indigenous staff roles with kinship relationships and social roles. While more research and evaluation are needed, disability funding bodies and service systems that facilitate these areas of promising practice may improve the accessibility of social care for Indigenous peoples.